Caracterización de residuos sólidos peligrosos durante la generación de energía eléctrica en la central térmica de Caballococha - 2018 - Arevalo Sales, Angela Gabriela (2021)
The Work was developed in the Thermal Power station of the city of Horse cocha, county of Marshal Ramón Castile, department of Loreto whose coordinates are: 3°54'21"S 70°30'59"O/-3.9058333333333,-70.516388888, with the objective to carry out a study of the types of dangerous solid residuals generated during the process of electric power generation in the city of Horse Cocha, the focus was of character participativo, through surveys, the investigation type was Quasi experimental, based on a statistic of the qualitative-quantitative type, the population that conformed people that work in the company in direct form or contractors which 113 people add, the initial sample conformed it 26 people and final 28 people, being reached the conclusion: In the thermal power station of Horse Cocha the generation of solid residuals, semisolids and dangerous liquids every year he/she goes in increase because the population grows and the demand of this service increases, like it could be proven work that during the three months of evaluation 336.8 kg of dangerous solid residuals and 4,860.8 kg of residuals semisolids and dangerous liquids were generated presently. It is needed to qualify the personnel continually on the handling, characterization and disposition of these residuals, according to that settled down in the Norma Technique Peruvian 900.058.2005 Code of colors for the devices of storage of residuals". During the time that I last the work, your basket 1 time per week to the personnel of the Thermal Power station, with that which improved in 95% the handling of these residuals, their segregation and characterization of the same ones.